Evaluating the quality of administrative training programs in the Directorate of Administrative Development at Tishreen University (Empirical Study) - زين العابدين دانيا; عيسى جميل (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The research aimed to evaluate the quality of the administrative training programs used in the Administrative Development Directorate at Tishreen University from the point of view of the administrative staff subject to the training courses held by the directorate under study according to the four dimensions: (trainer evaluation/training content evaluation/training environment evaluation/personal benefit evaluation) And to identify the impact of demographic variables (type of program / nature of the college / gender / age) on the responses of the administrative staff towards the quality of the training programs offered in the directorate. Where the descriptive analytical approach was adopted to collect secondary data through Arabic and foreign books and references, articles and periodicals issued in the field of research. The sample was randomly represented by 331 trainees from the administrative cadre of Tishreen University. It was determined according to the statistical sample law. The researchers concluded that the research sample tends to form a positive position in its evaluation of all aspects of the quality of training programs (trainers evaluation, content evaluation, personal benefit evaluation, environment evaluation) used in the Directorate of Administrative Development at Tishreen University, and that there are fundamental differences between the average answers of individuals The sample about each of the dimensions of the quality of the training program according to the demographic variables. The researchers concluded to direct the attention of training officials at Tishreen University to ways to activate and increase the effects achieved from administrative training programs by presenting a set of recommendations and suggestions.